Characterization of oxide interface charges in trench field stop IGBT - Sim, Zhi Lin (2024)
Oxide interface charges is an important factor to be assessed in technology development especially for a trench-gated power device. The plasma reactive ion etching process is used to form highly vertical trenches whereby the oxide-silicon interface is often saturated by large amount of oxide interface charges. These charges are responsible for the device performance, stability, and long-term reliability degradation. In this work, we characterized the charges by performing various %H2/N2 forming gas annealing in FS IGBT and determined the optimal anneal condition to intrinsically passivate the oxide interface charges.